Predicting the length of jury deliberations - Meitl, Michele Bisaccia (Journal of crime and justice, 2017)
Juries represent a critical part of the criminal justice process, often entrusted to reach guilt/innocence verdicts and also asked to decide between punishment options. Unfortunately, there has been little empirical criminological research examining the variation in the length of jury deliberations and the factors that may be related to this length. This exploratory study uses data from 144 federal criminal trials in the Eastern District of Texas over a six-year period in order to examine the length of these deliberations as well as some of the legal characteristics that may be associated with deliberation length, including the number and complexity of the charges, trial length, the time between offense and indictment, and whether defense counsel was retained or appointed. Results indicate that lengthy trials, those involving a higher number of counts, and cases where there is a long length of time between offense and indictment are related to longer deliberation times while economic crimes are related to shorter deliberation times. Additionally, the results suggest that privately retained counsel is related to longer deliberation times in non-economic compared to economic crimes. Future research directions are highlighted.